Influence of Maternal Fish Oil Supplementation on the Risk of Asthma or Wheeze in Children: A Meta-Analysis of Randomized Controlled Trials - Wu, Shaojing; Li, Changhong (Frontiers in Pediatrics, 2022)
Background Previous studies evaluating the influences of maternal fish oil supplementation on the risk of asthma or wheeze in children showed inconsistent results. We performed a meta-analysis or randomized controlled trials (RCTs) to systematically evaluate the efficacy of maternal fish oil supplementation for asthma or wheeze. Methods Relevant RCTs were obtained by search of PubMed, Embase, and Cochrane's Library databases. A random-effects model incorporating the potential publication bias was used to pool the results. Results Ten RCTs with 3,676 infants were included. Compared to control, maternal supplementation with fish oil was not associated with a reduced risk of asthma or wheeze [odds ratio (OR): 0.91, 95% confidence interval (CI): 0.72–1.14, P = 0.40] with mild heterogeneity (I2 = 28%). Subgroup analyses showed that maternal fish oil supplementation significantly reduced the risk of asthma (OR: 0.56, 95% CI: 0.35–0.91, P = 0.02; I2 = 0%), but not the risk of wheeze (OR: 1.12, 95% CI: 0.90–1.41, P = 0.32; I2 = 0%). In addition, maternal fish oil supplementation was associated with reduced risk of asthma or wheeze in high-dose studies (≥1,200 mg/d, OR: 0.65, 95% CI: 0.48–0.87, P = 0.003; I2 = 0%), but not in low-dose studies (<1,200 mg/d, OR: 1.10, 95% CI: 0.88–1.38, P = 0.39; I2 = 0%, P for subgroup difference = 0.005). Study characteristics such as the risk of the infants, timing of supplementation, and follow-up duration did not significantly affect the results. Conclusions Maternal fish oil supplementation may reduce the risk of clinically diagnosed asthma in children, particularly with high-dose fish oil.